Pengaruh Green Marketing dan Pengetahuan Terhadap keputusan Pembelian dengan Mediasi minat Membeli konsumen Sariayu Martha Tilaar di Kota Jember - Muhammad Dimyati; Maria Dewi Kartikasari; Hari Sukarno (e-Journal Ekonomi Bisnis dan Akuntansi, 2018)
Research aims to examine whether green marketing and knowledge influence on purchasing decision. Besides, it also aimed to analyze consumer buying interest mediation on green marketing effect and knowledge on purchasing decision of Sariayu Martha Tilaar in Jember City. Approach research used in this research is research quantitative, with a population of consumers Sariayu Martha Tilaar in Jember City. Sampling techniques used in this research was accidental sampling, with as many samples 104 people.The method of analysis the data used in this research was SEM (Structural Equation Model) analysis with confirmatory approach. Based on the research done can be concluded that variable green marketing and knowledge variables had significant influence on buying interest and purchasing decision, and buying interest had significant effect on the purchasing decision. Keyword: Green marketing, knowledge, buying interest, purchasing decision